Analisis Persamaan Merek Terkenal Tidak Sejenis Ditinjau Dari Hukum Merek : (Studi Putusan Mahkamah Agung Nomor 29 PK/Pdt.Sus-HKI/2016) - Rohman, Arif (JIPRO: Journal of Intellectual Property, 2021)
The granting of a brand to a product of goods or services can also prevent unfair business competition, with the brand of a product or service being able to distinguish its origin, quality and guarantee that the product is original. A high-priced product is usually not because of the product itself, but the influence of the brand. In the case obtained by the author, the panel of judges is of the opinion that the lawsuit for the cancellation of the mark is not accepted because the goods in dispute are not of the same type. The Supreme Court argues that until now there has been no Government Regulation as a follow-up to Article 6 paragraph 2 of Law Number 15 of 2001 concerning Marks. Based on the plenary meeting of the civil chamber as outlined in the Circular Letter of the Supreme Court Number 03/BUA.6/HS/SP/XII/2015, it has been agreed that the lawsuit for the cancellation of a mark which has essentially different similarities, the lawsuit must be declared not accepted and the verdict -the previous Supreme Court decision regarding the same mark for goods of a different kind is no longer guided by the guidelines; is a cumulative-critical legal case study that is based on a collection of information, the existence of cause and effect to then draw conclusions; Based on the description of the legal analysis above, the authors draw two conclusions, namely: 1. The decision of the Panel of Judges is not quite right. 2. The legal consequences of the Supreme Court's Decision Number 29 PK/Pdt.SusHKI/2016 which was decided with a verdict that cannot be accepted in the last legal effort of the PK, has permanent legal force.